2013
DOI: 10.1186/1757-2215-6-64
|View full text |Cite
|
Sign up to set email alerts
|

Pronuclear morphology evaluation for fresh in vitro fertilization (IVF) and intracytoplasmic sperm injection (ICSI) cycles: a systematic review

Abstract: The current systematic review was aimed to assess the effectiveness of the zygote morphology evaluation in fresh in vitro fertilization (IVF) and intracytoplasmic sperm injection (ICSI) cycles. All available studies reporting on zygote morphology and clinical and/or biological outcomes were analyzed. Forty studies were included in the final analysis. Fourteen different zygote scoring systems were employed. Zygote morphology correlated significantly with embryo quality and cleavage, blastocyst stage, embryonic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 55 publications
(244 reference statements)
0
20
0
Order By: Relevance
“…Early event assessment up to first cleavage of human embryos has been successfully correlated with subsequent embryonic development and/or implantation results [13][14][15]. But a complete picture of the morphometric changes within the oocyte before and after sperm injection for oocytes undergoing ICSI, together with the variability between oocytes, is still not clear.…”
Section: Introductionmentioning
confidence: 98%
“…Early event assessment up to first cleavage of human embryos has been successfully correlated with subsequent embryonic development and/or implantation results [13][14][15]. But a complete picture of the morphometric changes within the oocyte before and after sperm injection for oocytes undergoing ICSI, together with the variability between oocytes, is still not clear.…”
Section: Introductionmentioning
confidence: 98%
“…To date, literature data about the correlation among zygote morphology, biological and clinical outcomes are inconclusive, mainly due to different methods used for PN scoring system, the time of PN observation, and the insemination procedure [10].…”
Section: Discussionmentioning
confidence: 99%
“…Since the preliminary observations on PN formation and morphology, several scoring systems were proposed mainly taking into account the PN size, the NPB position and alignment [10]. Although the scores have been correlated with improved embryo development as well as with increased pregnancy and implantation, to date clinical data about the relationship between zygote morphology and IVF outcomes are con icting [10]. One of the main limitation of literature data is the use of different zygote grading systems.…”
Section: Introductionmentioning
confidence: 99%
“…15 from 20 studies (75%) also showed its correlation to blastocyst formation and quality. [16] PN scoring of 3 were considered abnormal due to lack of nucleolar precursor body (NPB) or only have one NPB. Those embryos show inability to cleave on second or third day.…”
Section: Discssionsmentioning
confidence: 99%